El despido en la legislación y en la jurisprudencia del Tribunal Constitucional y los Plenos Jurisprudenciales Supremos en materia laboral - Neves Mujica, Javier (Pontificia Universidad Católica del Perú, 2015)
The treatment of labor dismissal has been evolving in the legislation and in the jurisprudence. Whatis the current regulation of this subject? What is the procedure to ask for reparation in the case ofnon justified dismissal? These and other subjects related to this matter have been treated by the Constitutional Court and the Supreme  Court  inthe last binding precedents and in laboral courtrulings, respectively.Within this framework, the author illustrates us regarding the evolution of dismissal’s treatment in the legislation and recent jurisprudential pronouncements.

El tratamiento del despido laboral ha evolucionadotanto en la legislación como en la jurisprudencia. ¿Cuál es la actual regulación de dicha materia?¿Cuáles son las vías procesales para solicitar lasreparaciones en caso de despidos no justificados?Estas y otras cuestiones relacionadas han sido tratadas por el Tribunal Constitucional y la Corte Supremaen sus últimos precedentes vinculantes y plenos jurisdiccionales en materia laboral, respectivamente.En este marco, el autor nos ilustra respecto de la evolución del tratamiento del despido en la legislación y en los pronunciamientos jurisprudenciales recientes.
The dismissal in the legislation and in the jurisprudence of the Constitutional Court and the Supreme Court Rulings on labor cases
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01